2014
DOI: 10.1128/jvi.01380-14
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 1 Counteracts Viperin via Its Virion Host Shutoff Protein UL41

Abstract: bThe interferon (IFN)-inducible viperin protein restricts a broad range of viruses. However, whether viperin plays a role during herpes simplex virus 1 (HSV-1) infection is poorly understood. In the present study, it was shown for the first time that wild-type (WT) HSV-1 infection couldn't induce viperin production, and ectopically expressed viperin inhibited the replication of UL41-null HSV-1 but not WT viruses. The underlying molecular mechanism is that UL41 counteracts viperin's antiviral activity by reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 47 publications
6
68
1
Order By: Relevance
“…In this study, we found that UL41 targeted and reduced cGAS expression by degrading its mRNA. In addition, we and other researchers have demonstrated that UL41 is also involved in HSV-1-mediated immune evasion by targeting several IFN-stimulated genes (ISGs) (17,20,21). Therefore, UL41 is a broad innate immune inhibitor and can block cGAS/STING-mediated IFN signaling at multiple steps.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In this study, we found that UL41 targeted and reduced cGAS expression by degrading its mRNA. In addition, we and other researchers have demonstrated that UL41 is also involved in HSV-1-mediated immune evasion by targeting several IFN-stimulated genes (ISGs) (17,20,21). Therefore, UL41 is a broad innate immune inhibitor and can block cGAS/STING-mediated IFN signaling at multiple steps.…”
Section: Discussionmentioning
confidence: 97%
“…Samples were digested with DNase I and subjected to reverse transcription as previously described. The cDNA was used as the template for qRT-PCR to test the levels of IFN-␤ or cGAS mRNA, and 18S rRNA was used as an internal reference as previously described (17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…VP16 suppresses NF-B by binding to p65 and blocks IRF3-mediated transactivation by interfering with the formation of the CREB binding protein-IRF3 complex (39). The virion host shutoff protein abrogates the antiviral activity of some IFN-stimulated genes, such as those for tetherin, viperin, and zinc finger antiviral protein, by targeting their mRNA for degradation (40)(41)(42). ␥ 1 34.5 targets TBK1 to prevent its interaction with IRF3 and therefore inhibits IFN production (43).…”
Section: Discussionmentioning
confidence: 99%